Breakdown voltage reduction by field emission in multi-walled carbon nanotubes based ionization gas sensor - Saheed, M.S.M. (American Institute of Physics Inc., 2014)
Ionization gas sensors using vertically aligned multi-wall carbon nanotubes (MWCNT) are demonstrated. The sharp tips of the nanotubes generate large non-uniform electric fields at relatively low applied voltage. The enhancement of the electric field results in field emission of electrons that dominates the breakdown mechanism in gas sensor with gap spacing below 14 Î¼m. More than 90 reduction in breakdown voltage is observed for sensors with MWCNT and 7 Î¼m gap spacing. Transition of breakdown mechanism, dominated by avalanche electrons to field emission electrons, as decreasing gap spacing is also observed and discussed. Â© 2014 AIP Publishing LLC.